Surface Characterization and Catalytic Activity of Alumina and Alumina-Supported ZnSO Catalysts Prepared from Different Alumina Sources - Farid Sh. Mohamed (Adsorption Science & Technology)
Three alumina samples were prepared from different sources including aluminium isopropoxide, aluminium chloride and aluminium nitrate, and were then used to prepare supported ZnSO 4 catalysts via the impregnation method. The alumina and ZnSO 4 -supported samples were characterized by X-ray diffraction (XRD), FT-IR spectroscopy and nitrogen physisorption methods. Dehydration of 1-butanol and the cracking of cumene were undertaken over the prepared samples using a pulse microcatalytic technique. For a given alumina sample, the surface area and total pore volume decreased continuously with increasing ZnSO 4 content. Loading alumina samples with ZnSO 4 improved their dehydration and cracking activities. The source of alumina played a role in determining the surface acidity and catalyst activity of alumina and alumina-supported ZnSO 4 catalysts. Impregnation of ZnSO 4 on alumina samples resulted in an increase in the concentration of Lewis sites and the creation of Brönsted acid sites on their surfaces. The catalytic activity of the investigated catalysts was found to depend strongly on both the chemical composition and the type of acid site present on the catalyst surface.